Quality of Life of Opium Addicts after Treatment and Rehabilitation at Drop-in Center: Case Study the Expansion of the Royal Project for Sustainable Problem-Solving of the Opium Cultivation Areas - Nilaban, Sumnao; Nakayotinsakul, Yaowares; Khobthong, Ladda; Sangdueanchai, Sukuma; Singto, Thanya; Koontham, Sasiton; Inprom, Nantana; Boonchaipanitwattana, Sarayuth (Journal of Health Science of Thailand, 2023)
This descriptive research aimed to study the quality of life and compare quality of life for opium addicts after treatment and rehabilitation at drop-in centres. The purposive sampling was the method of selecting a sample group for this study. The sample group of 565 people was the opium addicts who used health service at drop-in centres in six districts in Thailand consist of Chai Prakan, Chiang Dao, Wiang Haeng, Mae Taeng, Omkoi, and Mae Ramat. The quality of life questionnaire for opium addicts was used as a tool for collecting data. The data were analyzed by descriptive statistics, percentage, mean, standard deviation, t-test, and one way ANOVA with scheffe’s method. It was found that (1) the quality of life for opium addicts after treatment and rehabilitation at drop-in centres showed that the overall result was at high level (average value=3.65). The results of well-being, psychological and emotional, social and health section were also high (average value=3.68-3.83). The results of career and income section were at moderate level (average value=3.21). (2) Opium addicts with different gender, occupation, income and duration of the receiving service at drop-in centers had significantly different quality of life (p<0.05).